PENINGKATAN HASIL BELAJAR SISWA DENGAN METODE MIND MAPPING PADA MATA PELAJARAN FIKIH DI MADRASAH IBTIDAIYAH - Arafat, Maulana; Suiani, Irda; Siregar, Agung Kaisar (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2019)
The problem in this study is the low of student’s learning outcomes of IV grade in MIN 6 Medan in fikih. It is caused by the ways of teacher’s teaching that needs to be modified, so it causes the student do not desire in following the lesson. This study is conducted to improve student’s learning outcome of IV grade in MIN 6 Medan in fikih by using mind mapping method. It uses Action Classroom Research consisting of two cycles, and every cycle consists of four lines, namely planning, implementing, observing and reflecting. Data collection techniques use observation, interviews, and documentation. Data analysis techniques are carried out qualitatively and quantitatively and questionnaire data is used to see the successful implementation of mind mapping methods in the classroom in order to improve student learning outcomes. Based on the results of the study, student learning outcome has increased where the average in pre-test is 39.04 then increation in the post-test cycle I is 75.58 and increation again in the post-test cycle II is 91.88. The percentage of students' classical completeness is 4.17% in the pre-test, 75% in the first cycle, and 95.83% in the second cycle. Based on the research result found, the conclusion is that the implementation of learning using the mind mapping method can improve student learning outcomes in fikih taught by teachers to students at the school.